KOMUNIKASI ORGANISASI KARYAWAN LANEXT COFFEE AND SPACE DALAM MEREDAM KONFLIK - Angeline Hanitya, Clarissa Michelle (Solidaritas, 2025)
This study collects data on the role of organizational communication at Lanext Coffee and Space in mitigating conflict among employees. It highlights how perceived conflict arises from different goals, beliefs, and attitudes within the organization, which can hinder the achievement of individual and collective goals. This study uses the formal and informal organizational communication theory by Pace and Faules, and uses qualitative methods, focusing on interviews to collect data on employee performance, organizational communication practices, and strategies for conflict resolution. The findings indicate that effective communication is essential in addressing and anticipating conflict, thus promoting a more harmonious work environment. The results of the study indicate that organizational communication at Lanext Coffee and Space is less effective. This study emphasizes the importance of clear structures and boundaries in corporate communication, which is important for all members of the organization to understand their roles and responsibilities. In addition, triangulation methods are used to validate the data collected, ensuring the credibility of the findings. Overall, this study contributes to the understanding of how organizational communication can serve as a tool to reduce conflict in the workplace environment. Keywords: Organizational Communication, Corporate Conflict, Conflict Resolution, Corporate Structure